Mathematical Reasoning Ability of Junior High School Students during the Covid-19 Pandemic in Solving HOTS Questions for Circle Material - Pamungkas, Haris Wahyu; Sutarni, Sri (Universitas Muhammadiyah Surakarta, 2021)
This study aims to determine the mathematical reasoning ability of junior high school students during the covid-19 pandemic in solving HOTS questions on circle material. This research uses descriptive qualitative method. The research subjects were six eight grade students at SMP Muhammadiyah 1 Kartasura. Data collection techniques using tests and interviews. Data analysis using data reduction techniques, data presentation, and drawing conclusions. The results showed that students with high mathematical reasoning abilities were able to fulfill all indicators of mathematical reasoning well and solve all questions correctly. Students with low mathematical reasoning abilities are only able to fulfill the indicators of presenting mathematical statements well and are not able to able to solve all questions correctly.